2019
DOI: 10.1080/21645515.2019.1627821
|View full text |Cite
|
Sign up to set email alerts
|

A natural language processing framework to analyse the opinions on HPV vaccination reflected in twitter over 10 years (2008 - 2017)

Abstract: In this research, we developed a natural language processing (NLP) framework to investigate the opinions on HPV vaccination reflected on Twitter over a 10-year period-2008-2017. The NLP framework includes sentiment analysis, entity analysis, and artificial intelligence (AI)-based phrase association mining. The sentiment analysis demonstrates the sentiment fluctuation over the past 10 years. The results show that there are more negative tweets in 2008 to 2011 and 2015 to 2016. The entity extraction and analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 13 publications
0
75
0
Order By: Relevance
“…The studies were published between 2015 [15] and 2020 [16], [17] as shown in Figure 2a. In line with the location of corresponding authors, half of the studies (n=6/12) were written in the US [18], [19], [20], [21], [22], [23], one each in the UK [16], in Spain [24], Netherlands [25], Sweden [15], China [17], and Italy [26] (Figure 2b).…”
Section: B Summary Of Study Characteristics 1) Year Of Publication and Country Of Originmentioning
confidence: 94%
“…The studies were published between 2015 [15] and 2020 [16], [17] as shown in Figure 2a. In line with the location of corresponding authors, half of the studies (n=6/12) were written in the US [18], [19], [20], [21], [22], [23], one each in the UK [16], in Spain [24], Netherlands [25], Sweden [15], China [17], and Italy [26] (Figure 2b).…”
Section: B Summary Of Study Characteristics 1) Year Of Publication and Country Of Originmentioning
confidence: 94%
“…Social media data analysis is also relevant during the COVID-19 outbreak to monitor how people react to the pandemic evolution over time (sentiment, anxiety, level of stress) as well as common beliefs, opinions [ 39 , 40 ], fears, or hopes regarding treatment or vaccines. Perhaps most importantly, identifying and combating the spread of “fake news” about COVID-19 is highly necessary in our modern digital society [ 41 , 42 ].…”
Section: Digital Data To Model Covid-19 Spread Evolution and Percepmentioning
confidence: 99%
“…Natural language processing-based techniques can also be used to identify and analyse social media posts on other drugs or clinical procedures for which an informed consent process is requested. We consider that natural language processing could potentially be a helpful tool to facilitate monitoring changes in community sentiment over time ( 45 ), through polarity indicators for example. We attained polarity scores for different posts, but without a larger sample size and validation, these scores remain somewhat arbitrary.…”
Section: Discussionmentioning
confidence: 99%